An Optimization of Composition Ratio among Triple-Filled Atoms in In0.3-x-yBaxCeyCo4Sb12 System. (22nd December 2013) - Kim, So-Young; Choi, Soon-Mok; Seo, Won-Seon; Lim, Young Soo; Lee, Soonil; Kim, Il-Ho; Cho, Hyung Koun
Abstract : Bulk nanostructured materials are important as energy materials. Among thermoelectric materials, the skutterudite system of CoSb3 is a representative material of bulk nanostructured materials. Filling a skutterudite structure with atoms that have different localized frequencies (also known as triple filling) was reported to be effective for lowering thermal conductivity. Among studies representing superior power factors, In-filled skutterudite systems showed higher Seebeck coefficients. This study sought to optimize the composition ratio among the triple-filled atoms in an In 0.3 - x - y Ba x Ce y Co 4 Sb 12 system. The composition dependence of the thermoelectric properties was investigated for specimens with different ratios among the three kinds of filler atoms in the In 0.3 - x - y Ba x Ce y Co 4 Sb 12 system. In addition, the process variables were carefully optimized for filled skutterudite systems to obtain a maximum ZT value.